ANALISA PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP COMPETITIVE ADVANTAGE DENGAN STUDENT ENGAGEMENT DAN UNIVERSITY CULTURE SEBAGAI VARIABEL INTERVENING - Junaydi Estefan (Business Accounting Review, 2015)
The purpose of this study was to know the affect of Transformational Leadership on Competitive Advantage through University Culture and Student Engagement as the intervening variables on private universities in Surabaya. In this study primary data were used by using questionnaire distributed into 6 private universities in Surabaya. This study used path modeling analysis technique with PLS tools. The result showed that there were positive and significant affect of Transformational Leadership on Competitive Advantage, Transformational Leadership on University Culture, Transformational Leadership on Student Engagement, University Culture on Competitive Advantage, and also Student Engagement on Competitive Advantage on private universities in Surabaya.